2003
DOI: 10.1002/jrs.1093
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond time‐resolved two‐photon absorption resonant four‐wave mixing in three‐dimensional spiropyran–PMMA samples

Abstract: The potential of four-wave mixing with two-photon absorption resonances for time-resolved studies of ultrafast processes triggering photochromic transformations in three-dimensional spiropyran-poly(methyl methacrylate) samples is demonstrated. Our experimental approach involves using 100 fs pulses of 800 nm fundamental radiation of a Ti:sapphire laser as a two-photon absorption resonant pump and 130 fs frequency-tunable pulses of an optical parametric amplifier as a time-delayed probe. The use of two-photon re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
(16 reference statements)
0
5
0
Order By: Relevance
“…UV light is generally used to induce ring-opening of the spiropyran form to the merocyanine form, which subsequently reverts back to the spiropyran form thermally or by irradiation with visible light. Recently, two-photon absorption in the near-IR region, using ultrafast laser pulses, has also been reported to induce interconversion between the spiropyran and the merocyanine forms. The depth of penetration, without losses due to one-photon absorption, and the localization of the excitation at the focal point, achieved by two-photon excitation, is attractive for recording devices and in biological applications, where deeper penetrating NIR light can be used to deliver small amounts of energy (20 μJ–7 mJ) in short pulses (50 fs–30 ps). , …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…UV light is generally used to induce ring-opening of the spiropyran form to the merocyanine form, which subsequently reverts back to the spiropyran form thermally or by irradiation with visible light. Recently, two-photon absorption in the near-IR region, using ultrafast laser pulses, has also been reported to induce interconversion between the spiropyran and the merocyanine forms. The depth of penetration, without losses due to one-photon absorption, and the localization of the excitation at the focal point, achieved by two-photon excitation, is attractive for recording devices and in biological applications, where deeper penetrating NIR light can be used to deliver small amounts of energy (20 μJ–7 mJ) in short pulses (50 fs–30 ps). , …”
Section: Introductionmentioning
confidence: 99%
“…14−16 The depth of penetration, without losses due to one-photon absorption, and the localization of the excitation at the focal point, achieved by two-photon excitation, is attractive for recording devices and in biological applications, where deeper penetrating NIR light can be used 16 to deliver small amounts of energy (20 μJ−7 mJ) in short pulses (50 fs− 30 ps). 17,18 The possibility to address a photochromic system with light of longer wavelengths has an important impact on the application of molecular switches in biointerfaces, drug delivery systems and molecular electronics. 2 For example, it has been demonstrated that spiropyrans can be used in the imaging of live cells.…”
Section: ■ Introductionmentioning
confidence: 99%
“…They have been exploited for a variety of applications, including materials for self-developing photography, actinometry, displays, transmission-controllable optical elements, and ophthalmic lenses . Having some of the largest two-photon cross-sections among the organic photochromic compounds, a prerequisite for application as memory elements capable of nondestructive readout, the SPs and SOs have become a favorite photoswitching unit for control of properties of composite materials, including polymers and liquid crystals. Some of the recent promising applications are photocontrol of protein conformation and enzyme activity, combination with magnetic ions and luminophores, ion detection, inclusion in host−guest compounds, modification of surface properties and membrane permeability, and incorporation in photoresponsive nanoparticles .…”
Section: Introductionmentioning
confidence: 99%
“…They identified characteristic features on the Rayleigh wing of the spectrum and assigned them to rotations of hydroxyl groups and second sound phonons. Konorov et al used a femtosecond time‐resolved two‐photon resonant FWM scheme to study the ultrafast processes triggering photochromic transformations in a three‐dimensional polymer matrix. The time‐resolved FWM measurements allowed visualization of the build‐up of coherences in the photochromic material on the leading edge of the pump pulse and indicated ultrafast phase relaxation on the femtosecond time‐scale in the bulk polymeric material.…”
Section: Applications To Condensed Phase Mattermentioning
confidence: 99%